Vocational Training Instructors’ Perceptions towards Transfer of Training: A Case Study - Bagale, Shiba (Journal of Technical and Vocational Education and Training, 2024)
This study is about how the participants of short-term training perceive training in the real context. The study is done with the help of an interview, where the participants are the trainers of short-term vocational training programs. The major finding of the training is that the participants have gained information about new methods and media. They perceived the training in a very positive way, and most of them understood the training as a booster of their professionalism. But the training was more focused on the instructional purpose than gaining skills. The main thing is that they realized the preparation and management of the training were very important. This study highlights that the training was more focused on the instructional skills and knowledge, and some presentations were made based on the skills. It also revealed that the implementation of instructional skills-based training in the participants' real workplace is challenging. Management of learning environment, preparation, and delivery are difficult to transfer in a real working situation.